Structural and Optical Properties of SmFe1-xMnxO3 Nanocrystallites - Singh A.K.; Hissariya R.; Srivastava S.; Chandel V.S. (My University, 2025)
SmFeO3 is an excellent host material as a potential agent for oxide-based spintronic applications that manifests unusual physical characteristics, namely spin reorientation transition (480 K) and spin-phonon coupling. The help of doping influences the spin reorientation transition. Here, we report the successful synthesis of SmFe1-xMnxO3 (x = 0, 0.10, 0.30, 0.50). Orthorhombic (space group: Pbnm) structures and lattice parameters of samples increase with Mn doping. In the case of 50% doped Mn, cation ordering (Fe–O-Mn) was confirmed by the ordering peak and unit-cell doubling. X-ray photoelectron spectroscopy approved the presence of Fe3+ cations and is distributed differently. The Raman spectra confirmed the phase formation. The band gap is changed from 2.51 to 1.21 eV, as confirmed by the change in sample colour and UV–visible spectroscopy in Mn-doping result. Our experimental findings suggest that with site substitution, the structural and optical properties of SmFe1-xMnxO3 change remarkably. © 2023, The Author(s) under exclusive licence to Sociedade Brasileira de Física.